2007
DOI: 10.1186/1748-717x-2-45
|View full text |Cite
|
Sign up to set email alerts
|

A phase III trial comparing an anionic phospholipid-based cream and aloe vera-based gel in the prevention of radiation dermatitis in pediatric patients

Abstract: Purpose: Radiation dermatitis is a common side effect of radiation therapy (RT). In severe cases, RT must be interrupted until the skin heals, which can compromise treatment. The purpose of the study was to compare an anionic polar phospholipid (APP)-based cream and an aloe vera-based gel to determine their effectiveness in preventing and treating radiation dermatitis. Patients and methods:Forty-five pediatric patients (median age, 11 years) with various diagnoses who received at least 23.4 Gy participated. AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 14 publications
0
29
0
4
Order By: Relevance
“…Numerous studies using different compounds such as corticosteroid, aloe vera, hyaluronic acid, sucralfate, biafine, moisturizing durable barrier cream, ascorbic acid, silver sulfadiazine, and calendula have been performed to identify a topical agent that prevents or minimizes the acute radiation dermatitis, but the results of most studies were negative or contradictory (Halperin et al, 1993, Williams et al, 1996, Fisher et al, 2000, Bostrom et al, 2001, Schmuth et al, 2002, Pommier et al, 2004, Merchant et al, 2007, Kirova et al, 2011, Hemati et al, 2012, Pinnix et al, 2012, Graham et al, 2013. A few topical agents demonstrated a superior efficacy in preventing acute radiation dermatitis in randomized phase Ⅲ trials (Schmuth et al, 2002, Pommier et al, 2004, however, there is no general agreement on the gold-standard approach for prevention or minimization of acute radiation dermatitis, and clinical practice seems to be varied across countries and institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies using different compounds such as corticosteroid, aloe vera, hyaluronic acid, sucralfate, biafine, moisturizing durable barrier cream, ascorbic acid, silver sulfadiazine, and calendula have been performed to identify a topical agent that prevents or minimizes the acute radiation dermatitis, but the results of most studies were negative or contradictory (Halperin et al, 1993, Williams et al, 1996, Fisher et al, 2000, Bostrom et al, 2001, Schmuth et al, 2002, Pommier et al, 2004, Merchant et al, 2007, Kirova et al, 2011, Hemati et al, 2012, Pinnix et al, 2012, Graham et al, 2013. A few topical agents demonstrated a superior efficacy in preventing acute radiation dermatitis in randomized phase Ⅲ trials (Schmuth et al, 2002, Pommier et al, 2004, however, there is no general agreement on the gold-standard approach for prevention or minimization of acute radiation dermatitis, and clinical practice seems to be varied across countries and institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately all these trials demonstrated that the treatment with Aloe vera gel possesses a very limited efficacy in the prevention of the toxic effects due to radiotherapy [289,290,291,292]. The current body of evidence leaves clinicians unable to provide comprehensive guidelines for prevention and management of acute radiation dermatitis.…”
Section: Pps As Protectors Against Toxic Effects Of Photo- Radio- Amentioning
confidence: 96%
“…APP cream and Aloe vera gel which were symmetrically applied within the irradiated field after each treatment. Unfortunately, the results of these studies showed that the anionic phospholipid-based cream was significantly more effective than Aloe vera gel in the prevention and treatment of radiation-induced dermatitis [42].…”
Section: Radiation-and Chemotherapy-induced Disordersmentioning
confidence: 99%